Applying an Interactive Quantitative-Qualitative Framework: How Identifying Common Intent Can Enhance Inquiry. (March 2013) - Hitchcock, John H.; Newman, Isadore
This article offers a conceptual discussion of a series of qualitative and quantitative research endeavors that share common underpinnings and purpose. The article demonstrates several commonalities between approaches with the hope of encouraging readers to allow research questions to guide methodological choices and avoid overemphasizing division between research paradigms. The current work offers an extension of ideas previously published in Human Resource Development Review (Newman & Hitchcock, 2011) to address a call to explore aspects of theory-building in the context of research methods (Reio, 2010). Specific ideas discussed here focus on commonalities between quantitative and qualitative work when dealing with the broad notion of generalization, and include connections between transferability, probabilistic generalization, naturalistic generalization, and external validity; commonalities between multiple (or collective) case studies and meta-analyses; and phenomenological perspectives and probability.